Detecting the impact of temperature on transmission of Zika, dengue, and chikungunya using mechanistic models. - Erin A Mordecai; Jeremy M Cohen; Michelle V Evans; Prithvi Gudapati; Leah R Johnson; Catherine A Lippi; Kerri Miazgowicz; Courtney C Murdock; Jason R Rohr; Sadie J Ryan; Van Savage; Marta S Shocket; et al. (Public Library of Science (PLoS), 2017)
Recent epidemics of Zika, dengue, and chikungunya have heightened the need to understand the seasonal and geographic range of transmission by Aedes aegypti and Ae. albopictus mosquitoes. We use mechanistic transmission models to derive predictions for how the probability and magnitude of transmission for Zika, chikungunya, and dengue change with mean temperature, and we show that these predictions are well matched by human case data. Across all three viruses, models and human case data both show that transmission occurs between 18-34°C with maximal transmission occurring in a range from 26-29°C. Controlling for population size and two socioeconomic factors, temperature-dependent transmission based on our mechanistic model is an important predictor of human transmission occurrence and incidence. Risk maps indicate that tropical and subtropical regions are suitable for extended seasonal or year-round transmission, but transmission in temperate areas is limited to at most three months per year even if vectors are present. Such brief transmission windows limit the likelihood of major epidemics following disease introduction in temperate zones.